PENGARUH EKUITAS MEREK TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE BLACKBERRY (Studi Empiris Pada Pusat Penjualan Handphone Di Plaza Matahari Lantai Dua Semarang) - Nugroho Saputro, 08.05.51.0113 (Students Journal of Economic and Management, 2014)
Customer buying decision making is a customerâs respond to providerâs strategies. Buying decisions made by costumer based on their beliefs is the right decisions. It would develop the customerâs confidence on their decision. There is a brand equity, if the costumers have brand awareness, perceived quality, brand association and loyalty. The objective of this research is to test the effect brand equity to the Blackberry brand mobile phone purchasing decision on mobile phone sales center on 2nd floor of Plaza Matahari Simpang Lima Semarang.The results of this study it can be concluded that ; brand awareness no effect on purchasing decisions, perceptions of the quality of a significant positive influence on purchasing decisions , brand association has no effect on purchasing decisions and brand loyalty of a significant positive influence on purchasing decisions. Keywords : Brand awareness , Perceived quality , Brand associations and Brand loyalty